2010
DOI: 10.1080/10610278.2010.510188
|View full text |Cite
|
Sign up to set email alerts
|

Control of nanospaces with molecular devices

Abstract: Cavitands and capsules define nanoliter spaces for recognition, isolation and reactions of small molecules. These systems are usually self-assembled and factors such as solvent size, stoichiometry, and packing factors determine what goes into the spaces. Here we examine two switching devices to control what and when guests get in and out of these hosts: bipyridyl-metal chelation and azobenzene photoisomerization. The effects are reversible by treatment with conventional chelating agents and brief heating, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, even with a reinforced intramolecular coordination of the hydroxy ligand, substitution at the endo site is still possible in the two redox states. The coordinating ability of L OH confirms that a redox switch at a metal cation can be activated if the affinity of a receptor for a guest is adequately tuned 22. In previous studies, it has been demonstrated that the control of molecular recognition in a cavity could be triggered by using a chemical,9a photochemical,9b or redox stimulus 6b.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…However, even with a reinforced intramolecular coordination of the hydroxy ligand, substitution at the endo site is still possible in the two redox states. The coordinating ability of L OH confirms that a redox switch at a metal cation can be activated if the affinity of a receptor for a guest is adequately tuned 22. In previous studies, it has been demonstrated that the control of molecular recognition in a cavity could be triggered by using a chemical,9a photochemical,9b or redox stimulus 6b.…”
Section: Resultsmentioning
confidence: 66%
“…The coordinating ability of L OH confirms that a redox switch at a metal cation can be activated if the affinity of a receptor for a guest is adequately tuned. [22] In previous studies, it has been demonstrated that the control of molecular recognition in a cavity could be triggered by using a chemical, [9a] photochemical, [9b] or redox stimulus. [6b, c, d] In this work, we coupled a redox stimulus with molecular recognition to induce motion in a molecular machine by switching the position of an internal ligand (endo/exo).…”
Section: Resultsmentioning
confidence: 99%
“…The return cis-to-trans transformation can be achieved thermally or by visible irradiation. In this way, different hosts such as cavitands and capsules can be rendered photoactive and more specifically the miniscule internal (yoctolitre) spaces available for chemical encapsulation can be controlled, which can ultimately lead to recognition, sequestration and reactivity of small molecules, depending on the host (9,10). Among different manifestations of azobenzene in supramolecular hosts, one of the most successful implementations was the development of photocrowns where an azobenzene unit was directly incorporated in the macrocyclic host or in 'butterfly' variants (7, 11 15).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we reported several reversible switches for container molecule complexes. [20][21][22][23][24][25] Typically, long guests such as azobenzene derivatives are well encapsulated by the homomeric cylindrical assembly 2.2 and smaller guests tend to favor hybrid capsule 1.2 (Fig. 1).…”
mentioning
confidence: 99%